Structural genome variants of Pseudomonas aeruginosa clone C and PA14 strains - Klockgether, Jens; Pust, Marie-Madlen; Davenport, Colin F.; Bunk, Boyke; Spröer, Cathrin; Overmann, Jörg; Tümmler, Burkhard (Frontiers in Microbiology, 2023)
Plasticity of Pseudomonas aeruginosa chromosomes is mainly driven by an extended accessory genome that is shaped by insertion and deletion events. Further modification of the genome composition can be induced by chromosomal inversion events which lead to relocation of genes in the affected genomic DNA segments, modify the otherwise highly conserved core genome synteny and could even alter the location of the replication terminus. Although the genome of the first sequenced strain, PAO1, displayed such a large genomic inversion, knowledge on such recombination events in the P. aeruginosa population is limited. Several large inversions had been discovered in the late 1990s in cystic fibrosis isolates of the major clonal lineage C by physical genome mapping, and subsequent work on these examples led to the characterization of the DNA at the recombination breakpoints and a presumed recombination mechanism. Since then, the topic was barely addressed in spite of the compilation of thousands of P. aeruginosa genome sequences that are deposited in databases. Due to the use of second-generation sequencing, genome contig assembly had usually followed synteny blueprints provided by the existing reference genome sequences. Inversion detection was not feasible by these approaches, as the respective read lengths did not allow reliable resolution of sequence repeats that are typically found at the borders of inverted segments. In this study, we applied PacBio and MinION long-read sequencing to isolates of the mentioned clone C collection. Confirmation of inversions predicted from the physical mapping data demonstrated that unbiased sequence assembly of such read datasets allows the detection of genomic inversions and the resolution of the recombination breakpoint regions. Additional long-read sequencing of representatives of the other major clonal lineage, PA14, revealed large inversions in several isolates, from cystic fibrosis origin as well as from other sources. These findings indicated that inversion events are not restricted to strains from chronic infection background, but could be widespread in the P. aeruginosa population and contribute to genome plasticity. Moreover, the monitored examples emphasized the role of small mobile DNA units, such as IS elements or transposons, and accessory DNA elements in the inversion-related recombination processes.